2021
DOI: 10.1093/tas/txab214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of beef genotypes on animal performance, carcass traits, meat quality, and sensory characteristics in grazing or feedlot-finished steers

Abstract: A 2-yr study was conducted to evaluate the effects of beef genotypes and feeding systems on performance, carcass traits, meat quality, and sensory attributes. A 2×2 factorial experiment was used to randomly allocate 60 steers in year 1 (YR1) and 44 steers in year 2 (YR2). The two beef genotypes evaluated were Red Angus (RA), and RA x Akaushi (AK) crossbreed. The steers were allotted to two finishing feeding systems: grazing, a multi-species forage mixture (GRASS) and feedlot finishing, conventional total mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 83 publications
(94 reference statements)
3
20
0
1
Order By: Relevance
“…Pellets were identical for both years and contained 36% crude protein (n536, Kalmbach Feeds, INC. Upper Sandusky, Ohio). The botanical composition of the diets was reported by Maciel et al (2021). The pasture consisted of an established mixed forage.…”
Section: Experimental Design and Diet Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pellets were identical for both years and contained 36% crude protein (n536, Kalmbach Feeds, INC. Upper Sandusky, Ohio). The botanical composition of the diets was reported by Maciel et al (2021). The pasture consisted of an established mixed forage.…”
Section: Experimental Design and Diet Characteristicsmentioning
confidence: 99%
“…The grazing period lasted 80 days in 2019 and 121 days in 2020. Experimental design and animal management were shared with Maciel et al (2021). Briefly, PAST samples were collected by randomly clipping three 0.25 m 2 quadrats to a 5 cm stubble using Gardena 8803 (Ulm, Germany) battery-operated harvest shears.…”
Section: Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental design for this study was reported by Maciel et al [ 35 ]. Briefly, this study was conducted over a period of two years (2019 and 2020) at the Michigan State University Upper Peninsula Research and Extension Center (UPREC) located in Chatham, MI (latitude: 46°20′ N, longitude: 86°55′ W; elevation: 271 m).…”
Section: Methodsmentioning
confidence: 99%